Oil Exploitation and Human Development of Tauramena, Colombia (2023)
Colombia, under the influence of enclave economies, has been driven to pursue the extraction of raw materials for export, as its primary source of income. These activities, mostly originating from foreign direct investment, may lead to socioeconomic and environmental problems and conflicts in the communities where they are conducted, even though they provide sizable royal bonuses. This article aims to examine the impact of oil exploitation on the human development of the residents of Tauramena municipality in Casanare department in the 2022. The study utilizes a qualitative-quantitative methodology that involves semi-structured interviews and surveys. An analysis of variance model (ANOVA) will be employed to estimate the findings. According to the results, oil exploitation has not statistical significance in the perception of human development or its components. In addition, it has a negative significance in public services, natural wealth, foreign populations, and security.